Greening governance - Bueren, Ellen van (IOS Press, 2013)
After twenty years of sustainable building policies, the issue of environmental impact of buildings and urban environments remains. Policy makers still have difficulties addressing the ambiguous, contested and dynamic goals encapsulated in the term ‘sustainable development’. How to decide between using zinc or PVC gutters, when knowledge and valuation of environmental risks of both keep changing? How can we accommodate urban growth, now that compact cities turn out to be urban heat islands? Greening governance identifies how policy makers can deal with these contested questions. The book draws on policy network theories that consider stakeholder interaction, negotiation and learning as conditions for policy success. By understanding these conditions from an evolutionary viewpoint it provides a new perspective for governance. The concepts of generative variety, selective retention and regeneration will help policy makers to prioritise and select contested alternatives while also focusing on more long term and ambitious policy goals. The book is of interest to policy makers and scientists concerned with both the practical and theoretical issues of sustainable built environments.